Use of biowaste to ameliorate chromium-contaminated soils to improve crop productivity - Anuradha Rai; Naveen Kumar Sharma; Vinod Kumar Singh; Ashish Rai; Vipin Kumar; Abhinav Kumar; Jay Shankar Singh; Sanjay Kudesia; Pradeep Kumar Rai (Waste Management Bulletin, 2024)
Increasing discharge of untreated industrial effluents has led to high metal loads in different environments. In the recent past Chromium (Cr) has emerged as a severe pollution to soil and aquatic ecosystems. Its global average load in soil is 54 ppm. Chromium has deleterious effects on crops and the subsequent food chain. If ingested, hexavalent chromium [Cr (VI)] is highly carcinogenic to faunal health. Here, we investigate the use of biowaste on chromium-contaminated soils to promote phytostabilization and overall improvement in crop productivity via decreased solubilization, restricted leaching, higher bioavailability of micronutrients, along with the efficient recycling of waste from the environment. Biowaste amendments facilitate complex processes such as stable compound formation after reacting to organic ligands, precipitation on surfaces, and ion exchange phenomenon; to improve fertility, physical health, and microbial activity in soil. The resulting improved soil quality promotes resettlement of vegetation and better plant growth and development. The potency of different biowastes to immobilize the hazardous metal(loid)s depends on their chemical nature, the extent of their degradation by microbes, their reaction in specific soil-type and concerned metal(loid)s. We need to develop different bio-remedial strategies to curtail the Cr-phytotoxicity, and ensure sustainable crop productivity.